Randomised comparison of electrode positions for cardioversion of atrial fibrillation. Issue 6 (1st June 1999) - Mathew, T P; Moore, A; McIntyre, M; Harbinson, M T; Campbell, N P S; Adgey, A A J; Dalzell, G W N
Abstract : OBJECTIVE: To compare the relative efficacy of anteroanterior v anteroposterior electrode pad positions for external cardioversion of atrial fibrillation. DESIGN: Prospective randomised trial. SETTING: Tertiary referral cardiology centre in the United Kingdom. PATIENTS: 90 patients undergoing elective cardioversion for atrial fibrillation. INTERVENTIONS: Cardioversion was attempted with self adhesive electrode pads with an area of 106 cm 2 placed either in the anteroanterior (AA) or anteroposterior (AP) positions. Initial shock was 100 J which, if unsuccessful, was followed by 200 J, 300 J, and 360 J if required. Peak current and transthoracic impedance were measured. MAIN OUTCOME MEASURES: Cardioversion success rate and energy requirements. RESULTS: Cardioversion was successful in 81% of the patients (73/90). There was no statistically significant difference in the cardioversion success rate (AA 84%, 38/45 patients; AP 78%, 35/45 patients; p = 0.42) or mean (SD) energy requirement for all patients (AA 223 (96.1) J; AP 232 (110) J) or for patients who were successfully cardioverted (AA 197.9 (82.4) J; AP 195.4 (97.2) J; p = 0.9) between the two pad positions. The mean transthoracic impedance (TTI) for the first shock (AA 77.5 (18.4) ohms; AP 73.7 (18.7) ohms; p = 0.34) was not significantly different between the two groups. TTI correlated significantly with body mass index, percentage body fat, and chest AP diameter. There was a progressive decrease in TTI with serial shocks. While aetiology and TTI were the two independent significant predictive factors for energy requirement, duration of atrial fibrillation was the only independent predictor of cardioversion success in a multivariate analysis. CONCLUSIONS: Electrode pad position is not a determinant of cardioversion success rate or energy requirement.